2002
DOI: 10.1038/sj.ejcn.1601396
|View full text |Cite
|
Sign up to set email alerts
|

Plasma deoxycholic acid concentration is elevated in postmenopausal women with newly diagnosed breast cancer

Abstract: Objective: High concentrations of plasma deoxycholic acid (DCA) are found in human breast cyst fluid and it has been hypothesised that this may be related to risk of breast cancer. The aim of this pilot study was to ascertain whether plasma bile acid concentrations were greater in women with breast cancer. Design: A case -control study comparing postmenopausal women with breast cancer with healthy controls was conducted. Subjects: Twenty Caucasian postmenopausal breast cancer patients were recruited at the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 18 publications
3
31
0
1
Order By: Relevance
“…Hence, bone or MG63 cell-derived DC was most likely taken up from serum and then released to the medium. The accumulation of bile acids from serum by .30-fold has been reported for breast cyst fluid and is discussed as a potential risk factor in breast cancer (6,7,12,13). We have shown that MG63 cells also take up and accumulate DC from medium, suggesting that bone tissue has similar capabilities for DC enrichment from serum.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Hence, bone or MG63 cell-derived DC was most likely taken up from serum and then released to the medium. The accumulation of bile acids from serum by .30-fold has been reported for breast cyst fluid and is discussed as a potential risk factor in breast cancer (6,7,12,13). We have shown that MG63 cells also take up and accumulate DC from medium, suggesting that bone tissue has similar capabilities for DC enrichment from serum.…”
Section: Discussionmentioning
confidence: 59%
“…Bile acids, another species of oxygenated cholesterol, have long been implicated in the tumorigenesis of colorectal cancer (4,5). Recent studies have shown that an increased concentration of bile acids in breast cyst fluid is indicative of a higher risk of developing breast cancer (6,7). It remained to be elucidated, however, which cell signaling pathways for tumorigenesis and breast cancer cell migration are triggered by bile acids.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Magnification bar: 10 lm as risk factors for developing breast cancer [17,18]. More recently, plasma bile acid concentrations were reported to be higher in postmenopausal women newly diagnosed with breast cancer, as compared to healthy controls matched for age and body mass index [16]. In addition, the current study reveals that chenodeoxycholic acid (CDCA) promotes the growth of MCF-7 cells.…”
Section: Discussionmentioning
confidence: 60%
“…Surprisingly, we and others have also found FXR expression in breast cancer tissue and breast cancer cell lines [13][14][15]. With regard to breast cancer development, the presence of high plasma levels of deoxycholic acid in postmenopausal breast cancer patients, as compared to healthy controls matched for age and body mass index, has been documented, suggesting that this bile acid might be involved in mammary gland carcinogenesis [16]. Moreover, accumulation of bile acids from serum has been reported in breast cyst fluid and has been discussed as a potential risk factor for developing breast cancer [17][18][19].…”
Section: Introductionmentioning
confidence: 48%